(untitled) (World Bulletin of Social Sciences, 2022)
This article substantiates the need for further improvement of the civil legislation of the Republic of Uzbekistan in force in the field of investment insurance. On the basis of a comprehensive analysis of civil legislation, it is proposed to make additions and changes aimed at strengthening the protection of the rights of investors in the existing legislative acts. This article is devoted to the introduction of new forms of investment insurance. This topic is chosen due to the lack of special research in the Republic of Uzbekistan on the legal regulation of investment insurance. The methodological basis of the article includes the empirical, historical, and comparative legal methods of scientific analysis. The determination of the main directions for improving the investment legislation of the Republic of Uzbekistan and the preparation of practical proposals and recommendations for improving this segment of national legislation based on international legal standards are the main results obtained by the author of the article in the process of research work. The main conclusions made by the author in the process of scientific work encompass the following: the issues of legal regulation of insurance of investment activities have not yet been sufficiently researched in Uzbekistan; currently there is no single international legal act regulating the process of insurance of investment activities; investment and insurance legislation of Uzbekistan needs further improvement